Peran Lazisnu Kecamatan Limpung dalam Pengumpulan dan Penyaluran Zakat, Infaq, dan Sedekah (ZIS) - Nidhom, Misbahun; Amam, Rofif; Hasanah, Sofiatul; Dermawan, Sigit; Safila, Ardian Yega; muamar_assidiqi (Jurnal Pengabdian Kepada Masyarakat, 2025)
This research aims to analyze the role, challenges, and strengthening efforts of the Nahdlatul Ulama Zakat, Infak, and Sadaqah Institution (LAZISNU) in Limpung District in managing community funds. The study employed a descriptive qualitative approach using observation, active participation, interviews, and documentation during the Field Practice Program (PPL). The findings reveal that LAZISNU Limpung plays a significant role through programs such as the NU Coin Movement, educational scholarships, health services, and social assistance. However, the effectiveness of these programs is hindered by limited socialization, low zakat literacy among the community, lack of human resources, and transparency issues in fund management. To address these challenges, several strategies are proposed: strengthening socialization, enhancing zakat literacy, ensuring transparent financial reporting, utilizing digital technology, and fostering collaboration with community leaders. These strategies are expected to increase community participation and strengthen sustainable community empowerment.